Reaching national Kyoto-targets in Germany by maintaining a sustainable development - Stefan Bayer; Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 2000)
Within this paper, we analyse the fulfilment of the Kyoto-emissions reduction com-mitment exemplary in Germany and its implication on long-term paths of all macro-variables. Germany, like all other industrial or Annex B coun-tries, has to reduce its emissions by 2010 and after what we call a "Kyoto-forever-scenario". We exemplary investigate tradable permits as reduction measures in a national OverLapping Generations (OLG)-model, where we change the discounting technique by using generation adjusted discounting (GAD) in comparison to conventional OLG-models. We show that within our model-framework Germany is able to develop along growing paths of e.g. GDP in sharp contrast to conventional results of OLG-simulations. At the same time, nowadays living generations have to share higher burdens in terms of lower GDP, per capita consumption and employment which can be interpreted, firstly, as contemporary costs for reaching sustainable paths and, secondly, contributions for internalising intertemporal external effects. However, all costs in terms of lower macro-variables for current living generations are overcompensated by higher future values of them. This effect can be interpreted as intertemporal application of full cost-bearance, or, in other words, the polluter pay principle which is oriented on the sustainability of GHG abatement.
Keywords: D58; D61; Q28; Q38; Q48; 330; OLG-models; discounting; sustainability; climate change; Kyoto targets; Klimaschutz; Luftreinhaltung; Treibhausgas-Emissionen; Emissionshandel; Overlapping Generations; Soziale Diskontrate; Wirkungsanalyse; Nachhaltige Entwicklung; Theorie; Deutschland